Cover Picture: Solvent‐Influenced Fragmentations in Free‐Standing Three‐Dimensional Covalent Organic Framework Membranes for Hydrophobicity Switching (Angew. Chem. Int. Ed. 13/2022). Issue 13 (1st March 2022) - Mohammed, Abdul Khayum; Al Khoori, Ayesha A.; Addicoat, Matthew A.; Varghese, Sabu; Othman, Israa; Jaoude, Maguy Abi; Polychronopoulou, Kyriaki; Baias, Maria; Haija, Mohammad Abu; Shetty, Dinesh
Abstract : Can we tune the physicochemical properties of free‐standing organic membranes without changing the building blocks or post‐synthetic modifications? The Research Article (e202200905 ) by Dinesh Shetty et al. demonstrates a novel pre‐synthetically controlled framework growth strategy to tune the hydrophobicity of 3D‐Covalent Organic Framework (3D‐COF) membranes. The hydrophobic 3D‐COF membrane shows potential use for the demulsification of an oil–water mixture, a significant environmental and water reuse issue.